Pengaruh Penggunaan Media Sosial Terhadap Tingkat Kognitif Gen Z: Berdasarkan Analisis Taksonomi Bloom: Penelitian - Muhammad Irvandi Permana; Iqbal Evandi Fauzi; Gusmaneli (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
Social media is an inseparable part of the daily lives of generation Z, this paper describes the use of social media affecting Gen Z's cognition through an analysis of six levels of cognitive domains in Bloom's Taxonomy revised by Anderson and Krathwohl, which describes the hierarchy of thinking skills from the most basic to the most complex. Thus increasing more clinical understanding due to the abundance of relevant information, improving critical thinking skills when used to analyze existing information, and encouraging Gen-Z creativity through the content produced.